Analysis of the concept of guilt: from conceptual divergence to its implications for nursing research - Reis, Hugo (2022)
Background: Guilt has been an object of study in several areas of knowledge, including nursing. However, this concept is defined differently across disciplines, which is one of the main obstacles to developing studies on this topic. Objective: This study results from a narrative literature review. It aims to present a conceptual analysis of guilt while reflecting on the need to study the definition of the concept based on the former carers’ experience of this phenomenon. Main topics of analysis: Definition of the concept of guilt in the light of philosophy, legal sciences, and nursing, and presentation of the need to map the concept as a key starting point for the production of scientific knowledge. Conclusion: The literature describes the concept of guilt as a multidisciplinary concept with multiple meanings. Mapping the concept of guilt in a specific population and context is a key starting point for developing future studies on this topic.